2019
DOI: 10.1016/j.jsv.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the turbulent boundary layer over a porous trailing edge for noise abatement

Abstract: The hydrodynamic and acoustic fields for a NACA 0018 with solid and porous trailing edge inserts are investigated. The porous inserts, covering 20% of the chord, are manufactured with metal foams with cell diameters of 450 and 800 μm and permeability values of 6 × 10 −10 and 2.7 × 10 −9 m 2. The experiments are performed at a chord-based Reynolds number of 2.63 × 10 5 and an angle of attack of 0 •. The porous trailing edge with higher permeability provides up to 11 dB noise attenuation with respect to the soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 84 publications
(119 reference statements)
4
86
0
Order By: Relevance
“…7 (b), where positive values refer to noise abatement with respect to the baseline case. As reported previously [15,39,40], metallic foams reduce noise only below a material-dependent cross-over f c . For the two metal foams used in the present study, namely d c = 450 µm and d c = 580 µm, the cross-over is respectively found at f c = 2.5 and 2 kHz approximately.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…7 (b), where positive values refer to noise abatement with respect to the baseline case. As reported previously [15,39,40], metallic foams reduce noise only below a material-dependent cross-over f c . For the two metal foams used in the present study, namely d c = 450 µm and d c = 580 µm, the cross-over is respectively found at f c = 2.5 and 2 kHz approximately.…”
Section: Resultssupporting
confidence: 73%
“…The application of permeable materials at the trailing edge also represents a promising TBL-TE noise abatement technique. Previous experiments report up to 11 dB noise reduction with respect to a reference (solid) case [14][15][16] for materials that establish flow communication between suction and pressure sides. This communication requirement could be fulfilled by applying homogeneous permeable materials with different micro-structures at the trailing edge: fiber felts [17], polyurethane foams [15], micro-perforated plates [18] or open-cell metal foams [19].…”
Section: Introductionmentioning
confidence: 95%
“…The obtained source maps were integrated over different regions of integration (ROI) [50,51] to exclude the influence of other sources outside of these areas. This technique is analogous to the source power integration (SPI) [17,22,[50][51][52][53][54][55][56][57][58][59] but considering the formulation of functional beamforming [21,22]. This integration process provides the sound emissions for each source.…”
Section: Acoustic Imaging Methods and Sound Propagationmentioning
confidence: 99%
“…There are different methods to reduce this noise by modifying the blade, which includes the use of flow permeable materials. Several studies on this passive modification exist, including experimental studies on brush-like or slitted trailing edge extensions [1][2][3], on fully porous airfoils [4,5] and on airfoils with trailing edges modified by metal mesh sheets [6] or porous foams [7][8][9]. In addition, the availability of 3D printing technologies enables the use of porous trailing edges manufactured via rapid prototyping [10].…”
Section: Introductionmentioning
confidence: 99%